The Conservation Constitution : The Conservation Movement and Constitutional Change, 1870-1930 - Smith, Kimberly K., 1966- (Book collections on Project MUSE., 2019)
"In The Conservation Constitution, Kim Smith examines how the Progressive Era conservation movement shaped constitutional doctrine. Most Progressive policies aimed at protecting natural resources would have been considered unconstitutional in the mid-nineteenth century. But by 1920, constitutional objections to the new conservation regime had been met and governmental authority to manage natural resources was written into constitutional law. Smith seeks to answer a central question - how did constitutional doctrine evolve to accommodate this expansion of government power over the environment - by exploring the evolution of constitutional doctrine supporting wildlife conservation, forest conservation, and pollution control, from the late nineteenth century through the 1920s. She highlights a string of important Supreme Court decisions usually overlooked in histories of this period, including Geer v. Connecticut, Light v. United States, United States v. Grimaud, Missouri v. Holland, Hunt v. United States, Missouri v. Illinois, and Georgia v. Tennessee Copper Co"--Provided by publisher.